Application of Cloud Computing Technology in Resource Sharing in Abubakar Tafawa-Balewa University, Bauchi - Basaka, Aminu Abubakar; Ishaku , Abubakar Adamu (Communicate: Journal of Library and Information Science, 2023)
The study investigated the adoption of cloud computing technology for resource sharing among Faculty libraries and the main university library. Our research questions were raised, among which are: the existing computer network available in the main library and the rationales for the adoption of cloud computing to share library resources with the faculties. Qualitative research method was adopted; Focus group method, University Librarian and other librarians from the faculties were used as sample size of the study. Guided interview constituted the instrument for data collection, while descriptive method was used to analyze the data collected. The finding revealed that LAN, WAN, CAN, Internet and Network were the existing computer networks in the library; another finding of the study shows that library use cloud computing to provide library and information services to its students only within the main library building, and the library is distance to faculties in which students finds it difficult where access to information must not be location specific. The major implication faced by the adoption of cloud computing in terms of cost, staff and maintenance were: budgetary issues which lead to inadequate training of staff and recruiting the right staff to do the job among others. Based on the forgoing, the major way to overcome budgetary issues in the adoption of cloud computing is for university library to solicit for grants from financial institutions like banks, NGOs, and other foundations, more so, since cloud services are usage based or pay as you go pricing, university Library should adjust the usage and cost of its IT services in an efficient way. University library can experience cost reduction and flexibility of cost. Keywords:,